Changes of ashwood pH-value during conventional drying - Straže, Aleš (Zbornik gozdarstva in lesarstva, 2003)
Changes of pH of sawn wood during conventional drying were studied. Green ashwood boards (Fraxinus excelsior L.), 25.4 mm in thickness, were exposed to 1 month air drying and to kiln drying using 7 schedules, reached by varying temperature (20°C, 30°C and 65°C) and relative air humidity (33% to 90%). Wood samples for pH and moisture content (MC) determination were taken in successive time interval at 3 board`s depths (1/10, 1/3 and 1/2 of thickness).MC was established gravimetrically. pH-value determination of solid wood water system by suspending wood dust into distilled water was used. The lowest used temperature and duration of drying procedure had not significant influence on wood pH. Wood acidification was confirmed at higher drying temperatures (30°C and 65°C), particularly with lower drying rates and prolongation of the procedure. Among all the factors, drying temperature had the greatest impact on the pH-value of wood.
Keywords: jesenovina; les; pH; sušenje